2014
DOI: 10.1016/j.prevetmed.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of canine parvovirus in flies (Diptera) at open and closed canine facilities in the eastern United States

Abstract: More than thirty years have passed since canine parvovirus (CPV) emerged as a significant pathogen and it continues to pose a severe threat to world canine populations. Published information suggests that flies (Diptera) may play a role in spreading this virus; however, they have not been studied extensively and the degree of their involvement is not known. This investigation was directed toward evaluating the vector capacity of such flies and determining their potential role in the transmission and ecology of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Interestingly the four puppies that were hEC infected and severely diseased were under 9,5 weeks old, suggesting that there could be an age effect but this effect was not observed between the age categories used in our study. Previously seasonality for CPV was described with the predominant occurrence of CPV in summer months while others reported spring and early summer as the seasons with the highest occurrence of CPV (Houston et al, 1996;Bagshaw et al, 2014). The prevalence of CPV and CCoV positive puppies in our study varied by season, with CPV risk increasing in winter and spring compared to summer, and CCoV increasing in winter.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Interestingly the four puppies that were hEC infected and severely diseased were under 9,5 weeks old, suggesting that there could be an age effect but this effect was not observed between the age categories used in our study. Previously seasonality for CPV was described with the predominant occurrence of CPV in summer months while others reported spring and early summer as the seasons with the highest occurrence of CPV (Houston et al, 1996;Bagshaw et al, 2014). The prevalence of CPV and CCoV positive puppies in our study varied by season, with CPV risk increasing in winter and spring compared to summer, and CCoV increasing in winter.…”
Section: Discussionsupporting
confidence: 45%
“…Logistic regression was also used to sort out which pathogens were associated with acute diarrhoea and/or severe clinical signs. For these pathogens logistic regression was used to assess the association with previously published risk factors for gastrointestinal infections in dogs, namely age, breed (purebred vs. mixed breed), gender, vaccination history (fully vaccinated vs. partially or not vaccinated), sampling season (Summer: June-August; Autumn: September-November; Winter: December-February; Spring: March-May), and whether the puppy originated from a highvolume dog breeder (Houston et al, 1996;Stavisky et al, 2011;Ling et al, 2012;Saevik et al, 2012;Dupont et al, 2013;Bagshaw et al, 2014;Grellet et al, 2014). Age was categorized in 2 groups: younger than 3 months and older than 3 months, as 3 months is the age at which maternal immunity is expected to have diminished to an insignificant level for the majority of puppies and at which the final puppy vaccines generally are administered in the Netherlands (Davis-Wurzler, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the genetic material of a number of hitchhiked microorganisms was already detected in flies, including food borne bacteria, e.g. Salmonella spp., and enteric viruses18192021. For example, Newcastle disease virus (NDV) RNA was detected in, and even virions were isolated from, flies collected in the vicinity of infected chickens.…”
mentioning
confidence: 99%
“…Subsequently, viremia occurs, which is associated with the isolation from a variety of organs and tissues, and then finally, CPV is excreted through the feces to the environment [ 27 ]. Recently, it has been also suggested that insect vectors, such as flies, play a role in the virus transmission in terms of indirect exposure to susceptible animals, which reflects the ability of CPV to persist in the environment with stable [ 4 ].…”
mentioning
confidence: 99%